Assessment of patient’s anxiety and expectation associated with hemodynamic changes during surgical procedure under local anesthesia - Dantas, Marcos Vinícius Mendes; Nesso, Bianca; Mituuti, Daniel Sagawa; Gabrielli, Marisa Aparecida Cabrini (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
AbstractIntroduction The dental patient’s anxiety and expectation may significantly alter their vital signs. The use of local anesthetics associated with a vasoconstrictor may also alter the vital signs of these patients, promoting hemodynamic changes that may result in emergency situations.Objective To evaluate the influence of anxiety of patients submitted to third molar extraction and the use of different anesthetic substances with adrenaline on their vital signs (oxygen saturation, heart rate, and systolic and diastolic blood pressure) in different moments.Material and method Forty patients answered the questionnaire of the Dental Anxiety Scale (Corah’s Scale) and fear (KleinKnecht’s Scale) and were submitted to third molar extraction in two surgical times for the use of articaine or mepivacaine, both associated with adrenaline. The results were analyzed by ANOVA followed by Tukey post hoc test, Student's t test, and Pearson's correlation coefficients (α=0.05).Result There was no significant differences in saturation or heart rate. The blood pressure showed significant variations during time for both anesthetics, however mepivacaine resulted in a longer postoperative time to restore blood pressure. Patients with high or moderate anxiety and high fear index were those who had positive correlations with the highest blood pressure values.Conclusion Anxiety and fear positively influence the increase in blood pressure. Mepivacaine promoted a greater resistance to the return of normal vital signs, especially blood pressure levels.

ResumoIntrodução A ansiedade e a expectativa do paciente odontológico podem alterar de forma significativa seus sinais vitais. Da mesma forma, o uso de anestésico local associado a um vasoconstrictor também alteram os sinais vitais desses pacientes, promovendo alterações hemodinâmicas que podem resultar em situações de emergência.Objetivo Avaliar a influência da ansiedade de pacientes submetidos à exodontia de terceiros molares e do uso de diferentes substâncias anestésicas com adrenalina sobre seus sinais vitais (saturação de oxigênio, pulsação e pressão arterial sistólica e diastólica) em diferentes momentos operatórios.Material e método Quarenta pacientes responderam os questionários da Escala de Ansiedade Dentária (Escala de Corah) e de medo (Escala de Kleinknecht) e foram submetidos à exodontia dos terceiros molares em dois tempos cirúrgicos para utilização de articaína ou mepivacaína, ambos associados com adrenalina. Os resultados obtidos foram analisados por ANOVA seguido do teste post hoc de Tukey, t de Student e coeficientes de correlação de Pearson (α=0,05).Resultado Não houve alteração significativa na saturação nem na frequência cardíaca. A pressão arterial apresentou variações significantes nos tempos aferidos para os dois anestésicos, entretanto a mepivacaína resultou em maior tempo de pós-operatório para o restabelecimento da pressão arterial. Os pacientes com muita ou moderada ansiedade e alto índice de medo foram os que tiveram correlações positivas com os maiores números pressóricos aferidos.Conclusão A ansiedade e medo influenciam positivamente no aumento da pressão arterial. A mepivacaína promoveu uma maior resistência ao retorno da normalidade dos sinais vitais, especialmente dos níveis pressóricos.
Avaliação da ansiedade e da expectativa do paciente associadas às alterações hemodinâmicas durante procedimento cirúrgico sob anestesia local
Keywords: Anxiety; fear; vital signs; blood pressure; local anesthetic; Ansiedade; medo; sinais vitais; pressão sanguínea; anestésico local